Web-based accommodation finder for students / Mona Sofiah @ Dewi Abd. Kahar - Mona, Sofiah @ Dewi (2003)
Web-based accommodation finder for students was developed for students of University of Malaya to provide a more efficient way for them to search for accommodation outside campus area. Nowadays, students usually search for accommodation from advertisements through newspapers at bus stop, bulletin boards ets of through friends. Many problems arise by searching in this way. Therefore, this system helps to eliminate some of these problems by enabling students to search from one source-the Internet. This system enables users to search for accommodation by location, number of rooms or rent price issued. Students may also obtain information on other organizations that offers accommodation services such as hostels. Other than that, landlords/accommodation occupants can advertise in order to find occupants. This system was developed by using the waterfall model methodology. Review on current systems has assisted in understanding how the system should interact with users. This is important to achieve the project goal which is to provide a reliable high-quality and efficient system to users.